PAUD Students Based on Prezi Media Using Assure Model - Asrowi, Hermia Anata Rahmana (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This research is aimed to develop learning media of prezi in order to improve the learningresult on the material recognizing part of body, its functions and movements to developrough and smooth motoric. Technique of collecting data was conducted throughobservation, interview, evaluation test, and documentation. Sources of data in this researchwere students of PAUD Al Hasanah Sukoharjo, teacher, researcher, and documents. Theresearch method used Research and Development using ASSURE model (Analyze learners,states objectives, select methods, media and material, utilize media and materials, requirelearner participation, and valuate and revise). Media was used to analyzed KI-KD and amaterial on recognizing part of body, its functions and movements to develop rough andsmooth motoric which then made by using prezi media. Prezi was validated by material andmedia experts. Based on the analysis of the research, it is concluded that learning media ofprezi on the material recognizing part of body, its functions and movements to developrough and smooth motoric using ASSURE model is well-qualified based on its material andmedia display format with the category of âvery properâ. In conclusion, the research showsthat there is improvement of learning result on the material using ASSURE model basedon prezi media.Keywords: Learning Media, Prezi, Learning Result, ASSURE model